1988
DOI: 10.1002/cne.902730105
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial cells of cajal in the canine colon: A special communication network at the inner border of the circular muscle

Abstract: The ultrastructure of the region shown to be essential for pacemaking activity of the circular muscle of the canine colon was studied. This region, at the inner border of the circular muscle, consists of a network of several layers of interstitial cells of Cajal type III. These are interconnected to one another and to the adjacent circular muscle cells by numerous gap junctions. Elsewhere in circular muscle, gap junctions are rare and small. In addition, interstitial cells are in close (often less than 20 nm) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
117
0
6

Year Published

1989
1989
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(127 citation statements)
references
References 18 publications
4
117
0
6
Order By: Relevance
“…This region contains a population of interstitial cells of Cajal thought to be the pacemakers (Berezin et al 1988;Langton et al 1989). We also tested the effects of Ba¥ on preparations in which the submucosal pacemaker cells were removed by dissection (ICM).…”
Section: Resultsmentioning
confidence: 99%
“…This region contains a population of interstitial cells of Cajal thought to be the pacemakers (Berezin et al 1988;Langton et al 1989). We also tested the effects of Ba¥ on preparations in which the submucosal pacemaker cells were removed by dissection (ICM).…”
Section: Resultsmentioning
confidence: 99%
“…The submucosal border of the inner circular muscle coat produces electrophysiological events called slow waves, which are synchronized with mechanical contractions of this tissue (BARAJAs-LoPEz et al, 1989;CONKLIN and DU, 1990;SANDERS et al, 1990;SERI et al, 1990). Previous electron microscopic studies have shown that there are layers of special cells connected with each other by gap junctions (BEREZIN et al, 1988). These cells formerly were generally referred to as the interstitial cells of Cajal (ICCs) (BEREZIN et al, 1988;WARD and SANDERS, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Previous electron microscopic studies have shown that there are layers of special cells connected with each other by gap junctions (BEREZIN et al, 1988). These cells formerly were generally referred to as the interstitial cells of Cajal (ICCs) (BEREZIN et al, 1988;WARD and SANDERS, 1990). However, the cytological differences between these cells and the cells called ICCs in rodents (COOK and BURNSTOCK,1976;THUNEBERG, 1982THUNEBERG, , 1989 were so great that discrepancies occurred concerning which kinds of cells were actually being investigated.…”
Section: Discussionmentioning
confidence: 99%
“…This nerve plexus was described by STACH (1972) and called the plexus entericus extremus, a terminology subsequently adopted by other authors (FAUSSONE PELLE-GRINI, 1983;CHRISTENSEN and RICK, 1987). The canine colon does not have an inner layer of specialized smooth muscle and, similar to most other mammals, has a dense plexus of nerve fibre bundles at the surface adjacent to the submucosa (BEREZIN et al, 1988).…”
Section: Discussionmentioning
confidence: 99%